Extracellular Vesicles for Therapeutic and Diagnostic Applications - Krishnan, Anand; Chithravel, Vadivalagan; Gangadaran, Prakash; Muthu, Sathish; Peacock, Ben (Elsevier, 2025)
Extracellular Vesicles for Therapeutic and Diagnostic Applications provides an introduction to exosomes and extracellular vesicles, including their unique properties and characterization, before detailing the most-utilized isolation, purification, and surface engineering techniques for their preparation as therapeutic and diagnostic agents.